Cardiac MRI: T2-Mapping Versus T2-Weighted Dark-Blood TSE Imaging for Myocardial Edema Visualization in Acute Myocardial Infarction - Naßenstein, K.; Nensa, F.; Schlosser, T.; Bruder, O.; Umutlu, L.; Lauenstein, T.; Maderwald, S.; Ladd, M. E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To assess the diagnostic accuracy of T2 mapping for the detection of myocardial edema in acute myocardial infarction (AMI), and to compare this diagnostic accuracy with that of the current standard for myocardial edema imaging, which is T2w dark-blood TSE imaging.Materials and Methods: 29 patients with AMI were examined at 1.5 T. For the visualization of myocardial edema, T2 maps, calculated from three T2w SSFP images, and T2w dark-blood TSE images were acquired in standard short- and long-axis views. Cine SSFP images were acquired for the analysis of left ventricular (LV) function and late gadolinium enhancement images (LGE) for the visualization of myocardial necrosis. The T2 maps as well as the T2w dark-blood TSE images were evaluated twice independently from the cine SSFP and LGE images. The presence or absence of myocardial edema was rated visually for each LV segment. As the standard of reference, the infarct zone was defined based on the cine SSFP and the LGE images.Results: In this segment-based analysis, T2 mapping showed a sensitivity of 82 % and a specificity of 94 % for the detection of edema in the infarct zone. T2w dark-blood TSE imaging revealed a sensitivity of 50 % and a specificity of 98 %. T2 mapping showed a higher intra-rater agreement compared to T2w dark-blood TSE imaging (κ: 0.87 vs. 0.76).Conclusions: T2 mapping allows for the visualization of myocardial edema in AMI with a high sensitivity and specificity, and features better diagnostic accuracy in terms of a higher sensitivity compared to T2w dark-blood TSE imaging.Citation Format:• Naßenstein K, Nensa F, Schlosser T et al. Cardiac MRI: T2-Mapping Versus T2-Weighted Dark-Blood TSE Imaging for Myocardial Edema Visualization in Acute Myocardial Infarction. Fortschr Röntgenstr 2014; 186: 166 – 172
Keywords: heart; MR imaging; T2 mapping; myocardial infarction